From “Koureion” [«Κουρείον»] to “Barbershop”: modernising local tradition through global trends - Papadima, Aspasia (My University, 2019)
Following its accession to the European Union in 2004, Cyprus underwent a number of transformations – including that in its visual language – which have been noticeably influenced by intercultural trends. Over the last decade or so, traditional barbershops, locally known as “koureion”, have been in decline, progressively replaced by Westernised hipster barbershops, a phenomenon that has altered the Cypriot landscape both linguistically and visually. The visual landscape, which comprises colour, typography, and distinct graphic elements, has been particularly affected, especially regarding barbershop signs. This new trend is worth observing for further semiotic analysis and interpretation. The evolving visual language appears to be strikingly gendered, based as it is on stereotypes and other features that promote contemporary representations of masculinity. Similarly, the use of English as a lingua franca on newer barbershop signage seems to embrace Europeanness, which reveals the increasing relevance of and stimulus from the West. Based on empirical research, using primary as well as secondary data, this study examines the shift in the local typographic landscape. With the aid of semiotic analysis of both graphic and linguistic communication, the present work investigates the ways in which the local visual language follows European cultural trends and adapts to globalisation in order to keep up with the zeitgeist.
Keywords: Typographic landscape; Barbershop signs; Multimodal typography; Gendered design; Cultural trends; Graphic design